Communication Strategies Used by Students in English Learning-teaching - John Okafor Diobi; Nashruddin Nashruddin (JELITA, 2023)
This study aims to examine the communication strategies used by students in the activity of English learning-teaching as a second language. This qualitative research was conducted using an ethnographic approach with spoken discourse of students as the object. Data was collected from 27 students in the 9th grade at Ifako International Secondary School as the informants. The research data were collected through observation and informal interview. The data were then analyzed using performance analysis technique, namely an analysis based on the speech that occurs naturally and the linguistic competence. This present study found that students used two communication strategies, namely verbal communication strategy and nonverbal communication strategy, in English teaching-learning activity. The results of this study indicate that students use communication strategies with four objectives, namely to maintain the communication, to express a certain intention, to master language competence, and to master certain forms of strategic competence.